Late Atlantic Settlement in Southern Portugal - Results of an excavation of a Mesolithic shell midden by the River Sado - Larsson, Lars (Current Swedish Archaeology, 1996)
The study of large settlement sites with graves from the Late Mesolithic has changed our conception of this period. In western Europe this kind of antiquity has long been known, and it is well represented in the coastal area of western Iberia. One settlement site —Popas de Sao Bento, near the River Sado in southern Portugal — has recently been excavated as part of a joint Swedish-Portuguese project. The results of the excavation give interesting perspectives on specific and general conditions in a broader geographical, chronological, and social context.